The SPD approach to deploy service‐based applications in the cloud. (11th September 2014) - Yangui, Sami; Tata, Samir; Orgun, Mehmet A.; Orgun, Atilla Elçi; Pieprzyk, Josef; Chefranov, Alexander; Shankaran, Rajan; Wang, Huaxiong; Zhuge, Hai
Summary Cloud computing is becoming more and more an essential component in the cyberspace system. In this context, Cloud providers offer a multitude of resources and services that constitute a heterogeneous ecosystem and a new economic model. However, several issues remain to be addressed so that the Cloud becomes an efficient part of the cyber‐physical system. In this paper, we propose to address a platform as‐a‐service (PaaS) drawback that we noted as part of our work on service‐based applications deployment in Cloud platforms. To deal with that, we propose a new approach that we called SPD approach to provision appropriate platform resources and ensure hosting and deployment of applications based on Service Component Architecture or business process orchestration (Business Process Execution Language) specifications in Cloud platforms. The SPD approach stands for the three main steps of the process that we have defined, that is, (1) slice the application deployables into a set of elementary services, (2) package them into our already developed service micro‐containers, and then (3) deploy the obtained service micro‐containers in a target PaaS provider. Our approach is a PaaS‐independent approach that allows developers to deploy service‐based applications on any PaaS regardless of its capabilities. To illustrate our approach and to experiment its performances, we provide two realistic use cases scenarios, that is, a Service Component Architecture‐based application and a Business Process Execution Language‐based process deployment in Cloud Foundry PaaS. Copyright © 2014 John Wiley & Sons, Ltd.